Implementasi Microsoft Access sebagai Pencatatan Akuntansi pada UMKM Rumah Makan Pak Teguh - Hendi, Hendi; Ming, Ming (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was carried out to assist Pak Teguh's Madura Satay Restaurant in Lumajang, a micro, small, and medium enterprise (MSMEs), in overcoming the problem of manual financial record keeping. Manual record keeping often leads to calculation errors and loss of transaction data. Therefore, a simple Microsoft Access-based accounting system was designed to assist in recording sales and purchase transactions and automatically generate financial reports. The implementation method included interviews and observations to analyze needs, system design, implementation, and evaluation of users. The results of the activity showed that the application of this system improved time efficiency and the accuracy of financial records. The system also made it easier for business owners to monitor their financial condition in real time. Thus, the use of Ms. Access as an accounting system proved to be effective in supporting SME financial management to be more accurate and structured.